Células mononucleares originárias da medula óssea e do tecido adiposo associadas ao plasma rico em plaquetas na cicatrização óssea em cães - Barbosa, Anna Laeticia da Trindade (2013)
Alternatives have been proposed to accelerate the tissue repair process, foremost among them the use of stem cells (SC). For implantation of these cells are needed biodegradable carriers, which allow better adhesion, provide a microenvironment suitable for adaptation and cell implantation site. The Platelet Rich Plasma (PRP) is an autologous source and cost of growth factors (GFs), which concentrates platelets and GFs released by them, accelerating bone formation and improving the quality of newly formed bone. It may be a carrier suitable for implantation of SC, therefore, not induce immune responses, and contains factors that induce osteoblastic differentiation. The goal of this work was to evaluate by clinical, biochemical, radiological and histological findings, the use of PRP associated with mononuclear stem cells (MoSC) in the cortical bone healing in dogs. Also proposed to elaborate a PRP protocol efficient in dogs by means of a small volume of whole blood standardize the use of two force plates simultaneously in orthostatic pattern, and comparing this kind with the use of a platform. To evaluate the effectiveness of this association, was used 30 adult dogs, female, mixed breed, weighing between 5 and 10 kg, separated by random draw in six treatments. Was made a failure elliptical 1,0x0,4cm medial cortical diaphyseal tibia of each animal, being completed in accordance with the proposed treatment: solution of sodium chloride 0,9% (G1), PRP (G2), the total fraction of mononuclear cells TFMC originated of bone marrow (G3), stromal vascular fraction - SVF derived of adipose tissue (G4), TFCM associated with PRP (G5) and SVF associated with PRP (G6). In the preoperative period was collected blood for preparation laboratory protocol of PRP, bone marrow collection and adipose tissue, and processing of fractions of MoSC. Were evaluated daily clinical degrees of lameness, radiological, girth before, and biomechanics in the immediate postoperative period, at 7, 14, 21, 30, 37 and 45 days, and biopsies at 15 and 45 days. In biopsy of 15 days, the failure was enlarged to 1,5x0,4cm and treatment redone, which is currently regarded as the immediate postoperative period in subsequent evaluations. The protocol of the PRP showed efficiency made, focusing on average 7,29 ± 3,21 times the original number of platelets from whole blood, from 7,5 ml of blood. The use of two force platforms simultaneously, was successful, without difference between using one or two platforms. In the X-ray analysis and biomechanical G2, G3, G5 and G6 groups were more effective in bone healing and support of the limb, followed by G4, and after G1. Histological evaluation showed higher degree of advancement scar G5 and G6, G4 in sequence and finally G1. Concluding that association MoSC and PRP is effective, being responsible for an early neoangiogenesis, accelerated osteogenesis, with better quality of bone formation, osteoblast density and intense. The groups G5 and G6 are the best adjuvant treatment of bone healing in dogs, followed by G2, after G3, G4 then, and lastly G1.